Phylogeography of vertebrates on the Sunda Shelf: a multi‐species comparison. (13th January 2015) - Leonard, Jennifer A.; den Tex, Robert‐Jan; Hawkins, Melissa T. R.; Muñoz‐Fuentes, Violeta; Thorington, Richard; Maldonado, Jesus E.; Heaney, Lawrence
Abstract Aim Pleistocene environmental fluctuations had well‐characterized impacts on the patterns of within‐species divergences and diversity in temperate habitats. Here we examine the impact the Pleistocene had on widely distributed forest vertebrates in a tropical system where the distribution of the habitat was affected by those fluctuations. Location Sundaland, tropical Southeast Asia. Methods We conducted a comparative phylogeographical analysis of 28 non‐migratory, forest‐dependent vertebrates, for which we constructed rooted, intraspecifc phylogenies based on mitochondrial DNA sequences of individuals from at least the three major landmasses in the area (Borneo, Sumatra and the Malay Peninsula) and compared them to hypothetical phylogenies based on independent geological data and climate models regarding connections and relationships between the major landmasses of Sundaland. Java was included where possible. We dated the phylogenies to determine whether patterns of differentiation were concordant across species. Results In most species, populations on the Malay Peninsula and Sumatra were most closely related, and sister to those from Borneo. The dates of these divergences, however, varied extensively between species. Borneo harbours multiple deeply divergent lineages of many species compared to the diversity within those species. Javan populations of several birds were most divergent relative to those from the rest of the Sunda Shelf. Main conclusions These results suggest a dynamic history, including recurrent population extinctions and replacements and a strong priority effect for local populations. The close relationship between populations in Sumatra and the Malay Peninsula supports the existence of forest on the exposed shelf during the Pleistocene at many different times, and suggests that proximity was more important than the presence of palaeorivers for dispersal of forest taxa between landmasses.